Protein Thiol Modifications Visualized In Vivo - Leichert, Lars I; Jakob, Ursula (PLOS Biology, 2004)
A differential thiol-trapping technique combined with two- dimensional gel analysis has been developed and used to visualize thiol-disulfide exchange reactions, which act as switches in redox-regulated proteins.